Correlates of Elevated Interleukin-6 and 8-Hydroxy-2′-Deoxyguanosine Levels in Tracheal Aspirates from Very Low Birth Weight Infants Who Develop Bronchopulmonary Dysplasia - Chien-Chou Hsiao; Jui-Chih Chang; Lon-Yen Tsao; Rei-Cheng Yang; Hsiao-Neng Chen; Cheng-Han Lee; Ching-Yuang Lin; Yi-Giien Tsai (Pediatrics and Neonatology)
Bronchopulmonary dysplasia (BPD) remains the most common complication of very low birth weight (VLBW) preterm infants, and inflammatory regulation plays a role in the development of the BPD. Interleukin-6 (IL-6) has an important role in airway inflammation and therefore can be used as a marker of airway injury. The study aimed to compare the changes between IL-6 and oxidative stress marker with 8-hydroxy-2′-deoxyguanosine (8-OHdG) from serum and tracheal aspiration (TA) in VLBW preterm infants following development of BPD. Methods: This birth cohort study enrolled 80 VLBW preterm infants, including 26 who developed BPD. All infants completed the study and survived at 36 weeks postmenstrual age. IL-6 and 8-OHdG concentrations from serum and TA on Day 1 and Day 28 after birth were measured using immunoassay. Results: IL-6 and 8-OHdG in serum and TA were higher in the BPD group than in the non-BPD group on the 1st day after birth (p < 0.05). The IL-6 and 8-OHdG levels in TA fluid were persistently increased on the 28th day of life in the BPD group (p < 0.05). The TA IL-6 was positively correlated with 8-OHdG levels on the 1st day (r = 0.64, p < 0.05) and 28th day of life (r = 0.76, p < 0.05). Based on receiver operating characteristic curves as a predictor of BPD development, TA IL-6 (cutoff, 456.8 pg/mg) had 81.5% sensitivity and 77.8% specificity, whereas TA 8-OHdG (cutoff, 4.4 ng/mg) had a sensitivity of 81.5% and a specificity of 64.4%. Conclusion: Persistent inflammation with oxidative DNA damage in the respiratory tract may be a crucial mechanism in BPD.